A new beamline for hard X-ray tomographic microscopy at the Spanish Synchrotron ALBA. Issue 1 (1st December 2022) - Mittone, Alberto; Ribó, Llibert; Patera, Alessandra; Campmany, Josep; Colldelram, Carles; Nicolás, Josep
Abstract: The BL31-FaXToR is a new beamline currently under construction at the third generation synchrotron facility ALBA, dedicated to hard x-ray micro-tomography. The beamline will provide the opportunity to perform 3D imaging within sub-seconds time resolution, working under mono- or white-beam conditions. A dual detection system is foreseen at the top of an innovative end-station design in order to perform fast imaging with a multi-scale approach. In this paper, we provide an overview of the new beamline design and of the expected performances. Raytracing and phase-contrast imaging simulations have been used to optimize the optical design. The beamline will be fed by a 2.5T multipole wiggler with a critical energy of 14.7 keV. A double multilayer monochromator (DMM) covers an energy range between 8 to 50 keV with a bandwidth up to 3.5%. The DMM crystals can be shifted out of the beam path to operate in filtered white beam modality with higher energies spanning from 30 to 70 keV. Multiple filtering configurations will be used to optimize the spectra according to the specific experimental settings. The beamline will serve different scientific communities, including material science, biomedical, paleontology, earth science, cultural heritage etc. FaXToR is expected to start user operations by the beginning of 2024.